Acute Hepatitis after Ingestion of a Preparation of Chinese Skullcap and Black Catechu for Joint Pain - Charilaos Papafragkakis; Mel A. Ona; Madhavi Reddy; Sury Anand (Case Reports in Hepatology)
Many herbal preparations are routinely used and have been occasionally associated with a wide range of side effects, from mild to severe. Chinese skullcap and black catechu are herbal medications commonly used for their hepatoprotective and other properties. We report a case of acute toxic hepatitis associated with ingestion of Chinese skullcap and black catechu in one preparation for the alleviation of joint pain.